The Validity of A Sale and Purchase Agreement Via The Internet Reviewed From A Civil Law Perspective - Made Ayu Gita Lestari; I Nyoman Bagiastra (West Science Interdisciplinary Studies, 2024)
This examination means to decide the legitimacy of deals and buy arrangements through the Web from a common regulation point of view. The sort of exploration utilized is standardizing juridical. The nature of this research is descriptive and qualitative. Document study methods derived from relevant literature studies on the issues discussed were used in the process of data collection. The exploration results show that the legitimacy of a deal and buy understanding through the web should have a similar legitimacy as a regular understanding as long as it very well may be demonstrated and meets the arrangements in Article 1320 of the Common Code. The reason for legitimacy happens if the two of them commonly concur and there is an expression of understanding between the purchaser and merchant in conveying in regards to the proposal of merchandise and the determination of the ideal products and both have concurred that there is an arrangement.